2017
DOI: 10.1002/joc.5390
|View full text |Cite
|
Sign up to set email alerts
|

The role of monsoon low‐level jet in modulating heavy rainfall events

Abstract: Monsoon low‐level jet (MLLJ) is an important component of Asian summer monsoon circulation, which is responsible for large‐scale distribution and variability of rainfall over the Indian subcontinent. The evolution of MLLJ characteristics prior to heavy rainfall days and its changes which lead to instances of heavy rainfall over the south‐western coast of India are studied. The European Centre for Medium Range Weather Forecasts (ECMWF) re‐analysis data and India Meteorological Department (IMD) rainfall data dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Modelling efforts using the planetary boundary layer (PBL) model (Krishnamurti et al ., ; ) have successfully reproduced observed features of the Somali jet, such as its curvature, peak intensity, and position. Many other numerical studies have reported the significance of the Somali jet as a cross‐equatorial moisture‐flux feeding mechanism for the ISM and determined its role in creating convective instabilities required for triggering heavy events over the west coast of India (Raymond, ; Xavier et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Modelling efforts using the planetary boundary layer (PBL) model (Krishnamurti et al ., ; ) have successfully reproduced observed features of the Somali jet, such as its curvature, peak intensity, and position. Many other numerical studies have reported the significance of the Somali jet as a cross‐equatorial moisture‐flux feeding mechanism for the ISM and determined its role in creating convective instabilities required for triggering heavy events over the west coast of India (Raymond, ; Xavier et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…BLJs have maximum wind speeds in the BL and are usually explained by the inertial oscillation of ageostrophic winds (Blackadar, 1957) or baroclinicity associated with the terrain (Holton, 1967) or a combination of the two (Du & Rotunno, 2014; Du et al, 2014; Shapiro et al, 2016). The SLLJs have been observed over many regions of the world (e.g., Matsumoto et al, 1971; Squitieri & Gallus, 2016; Xavier et al, 2018; Xue et al, 2018). Numerous studies documented that the SLLJ is one of the important factors contributing to heavy rainfall production over south China and its vicinity (Chen & Yu, 1988; Du & Chen, 2018; Tao & Chen, 1987), through transporting warm, moist air from the tropical oceans, destabilizing the environment, and providing convergence at the terminus of the SLLJ (Chen et al, 1994; Tao & Chen, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Except large-scale circulation like prevailing westerlies, the coastal regions are featured with complex small-scale circulations. For instance, the low-level jet (zonal winds with high speed) contributes to rainfall in coastal regions in Asia (Xavier et al, 2018). The orographic effects enhance the precipitation over coastal mountain regions such as the west coast of NA and EU, and the southeast coast of RU (James and Houze, 2005).…”
Section: Own Region and Foreign Contributions To Depositionmentioning
confidence: 99%
“…The mass of aerosols arriving at the coasts of North American (NA) is comparable to that emitted domestically (Yu et al, 2012). Air pollution from Asia contributes to the PM 2.5 concentration in the western US by 1.5 µg m −3 (Tao et al, 2016), the O 3 concentration by 3-10 ppbv (Zhang et al, 2009(Zhang et al, , 2008Yienger et al, 2000;Reidmiller et al, 2009;Jacob et al, 1999;Brown-Steiner and Hess, 2011) and the peroxyacyl nitrate (PAN) concentration by 26 ppbv (Berntsen et al, 1999) in spring. The long-range transport of air pollution from NA is estimated to contribute 3-5 ppb (7 %-11 %) to the O 3 concentration in the EU annually (Auvray and Bey, 2005;Guerova et al, 2006;Derwent et al, 2004;Li et al, 2002) and the increment can reach 25-28 ppbv during particular events (Guerova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%